Geothermal sections of the earth's crust and upper mantle of the Black Sea and its northern border - R.I. Kutas (Геофизический журнал, 2011)
Results of measurements of heat flow and mathematical simulation of geothermic state of the lithosphere along two profiles, crossing the western and the eastern depressions of the Black Sea and flanking northward tectonic structures of different age have been presented. It has been shown that considerable variations of temperatures and heat flow within the lithosphere by lateral, depth and temporally are related to both geodynamic processes, accompanied by intensification of heat evacuation from the Earth interior during the stages of activization of tectono-magmatic activity and violation of heat transfer conditions and distribution of radiogenic heat sources in the Earth’s crust, stipulated by special features of its structure and evolution. Great effect on distribution of surface heat flow in the Black Sea basin is produced by tectonic reconstruction of the lithosphere since Late Meso-Cenozoic, accumulation of thick terrains of young sediments, formation of thrust faults, dynamics of fluids et al. Anomalously low heat flows in the Black Sea megadepression are related to sedimentation of thick terrains of Pliocene-Quaternary formations. Situation changes with depth. The mantle component of heat flow has maximal values under «granitless» depressions of the Black Sea. Within their limits isotherms occupy superior position. The thickness of geothermic lithosphere changes from 80-90 km under the West Black Sea and East Black Sea Depressions to 180-200 km under the south slope of the East European Platform. Position of geothermic asthenosphere has been compared to the results of seismotomographic studies. In behavior of geothermic asthenosphere and the layer of decreased seismic velocities in the upper mantle some general regularities, complicated by peculiarities of geological development of separate tectonic elements can be traced.